Hypertrophic Osteopathy Secondary to Pulmonary Metastases from Breast Carcinoma - Correa, Ricardo Andrés; Giraldo, Juan Carlos (Spei Domus, 2015)
Purpose: this article aims to report the findings of a clinical case of hypertrophic osteopathy. Topic: hypertrophic osteopathy is a rare paraneoplastic disorder associated with painful overgrowth of the periosteum of long bones, usually triggered by primary or metastatic lung tumors. Development: the case of a 12-year-old Rottweiler with hypertrophic osteopathy associated with pulmonary metastases from breast carcinoma is presented. Conclusions: clinical and radiographic findings and therapeutic possibilities are discussed.